Management of Salt Affected Soils for maximizing productivity - Kaur, Ramanjit; Singh, Ramesh K.; Buttar, G S; Rajni, Rajni (Indian Farming, 2016)
In salt affected soils, there is excess of sodium salts or predominance of sodium among exchangeable faxes. Such soils are categoused under degraded land. Soil degradation causes about 12% loss to the production system in our country. Thus there is on urgent need to douse and adobe ways and means to amend and letter use of saline and alkali soils for improving then productivity.